A g-C3N4 supported palladium nanocatalyst and its preparation method and application
In the preparation of g-C3N4-supported palladium nanocatalysts, the nucleation and growth of palladium particles are adjusted by DMF and water molar ratio in the solvent to form a palladium nanocatalyst with tetrahedral morphology, the complex preparation of existing palladium nanocatalysts is solved. and the problem of uncontrollable shape, the effect of efficient catalytic hydrogen reduction of nitrobenzene for preparation of aniline is achieved, and it has good stability and recyclability.
Patent Information
- Application Number
- CN202310144403.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-02-21
- Publication Date
- 2025-02-11
- Estimated Expiration
- 2043-02-21
AI Technical Summary
The existing palladium nanocatalyst preparation methods are complex, the load is small, and the shape of the palladium particles is uncontrollable, which affects the catalytic performance.
By mixing g-C3N4 solution, palladium source, bromide and coordination agent for reduction reaction, a g-C3N4 supported palladium nanocatalyst was prepared, and the nucleation and growth of palladium particles were adjusted using the DMF and water molar ratio in the solvent to form Palladium nanocatalyst for tetrahedral morphology.
A simple one-step preparation of palladium nanocatalysts is realized. The shape of palladium particles is controllable and the surface activity is high. The conversion rate and selectivity of aniline prepared by catalytic hydrogen reduction nitrobenzene reaches 100% and 99.9%, and it has good stability and cyclability. sex.
Smart Images

Figure CN116139907B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of catalyst technology, and in particular to a g-C3N4 supported palladium nanocatalyst and a preparation method and application thereof. Background Art
[0002] At present, the main preparation method of aniline is to reduce nitrobenzene, and the methods for producing aniline by nitro reduction include iron powder reduction method, alkali sulfide reduction method, catalytic hydrogenation method, hydrogen transfer reduction method, etc. The iron powder reduction method and the alkali sulfide reduction method are prone to produce a large amount of wastewater and toxic sludge during the reduction process. The hydrogen transfer reduction method often uses hydrazine hydrate as a hydrogen donor, which is highly toxic and not conducive to large-scale production. It is reported that platinum, palladium, gold and ruthenium-based metal-based catalysts are often used for catalytic hydrogenation reactions, but the performance of Pd nanocrystals is affected by their size and shape. When the synthesis is mainly controlled by thermodynamics, the shape of palladium particles in the supported palladium nanocatalyst is uncontrollable, and Pd crystals tend to form spherical or quasi-spherical shapes. The reduction rate during preparation will also affect the size of Pd particles. Therefore, the market usually adopts the method of synthesizing metal nanoparticles of a certain morphology first and then using the impregnation method to achieve loading on the surface of a certain type of carrier. However, this method has many disadvantages, such as cumbersome steps, small loading amount, and easy aggregation. Summary of the invention
[0003] The purpose of the present invention is to provide a g-C3N4 supported palladium nanocatalyst and a preparation method and application thereof.
[0004] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:
[0005] The present invention provides a method for preparing a g-C3N4-supported palladium nanocatalyst, comprising the following steps:
[0006] The g-C3N4 solution, palladium source, bromide and coordination compound are mixed and then subjected to reduction reaction to obtain the palladium nanocatalyst.
[0007] Preferably, the g-C3N4 solution contains g-C3N4 and N,N-dimethylformamide aqueous solution; the mass volume ratio of the g-C3N4 to the N,N-dimethylformamide aqueous solution is 620-630 mg: 10-22.5 mL.
[0008] Preferably, in the N,N-dimethylformamide aqueous solution, the molar ratio of N,N-dimethylformamide to water is 0.5-1.5:0-7.
[0009] Preferably, the palladium source is palladium acetylacetonate or palladium chloride; the bromide is sodium bromide or potassium bromide; and the ligand is molybdenum hexacarbonyl.
[0010] Preferably, the mass ratio of the palladium source to g-C3N4 is 40-50:620-630.
[0011] Preferably, the mass ratio of the bromide to g-C3N4 is 70-90:620-630.
[0012] Preferably, the mass ratio of the compatibility substance to g-C3N4 is 20-40:620-630.
[0013] Preferably, the temperature of the reduction reaction is 70-90° C., and the time of the reduction reaction is 10-12 hours.
[0014] The invention provides a g-C3N4-loaded palladium nanocatalyst obtained by the preparation method.
[0015] The present invention also provides the use of the g-C3N4 supported palladium nanocatalyst in catalyzing the reduction of nitroaromatics by hydrogen to prepare aniline.
[0016] The present invention has the following advantages:
[0017] The present invention provides a method for preparing a g-C3N4-supported palladium nanocatalyst, comprising the following steps:
[0018] The g-C3N4 solution, palladium source, bromide and ligand are mixed and then subjected to reduction reaction to obtain the g-C3N4-loaded palladium nanocatalyst. The catalyst preparation method provided by the present invention has a simple preparation process and is completed in one step. It is not necessary to first synthesize palladium tetrahedral nanoparticles and then load the palladium particles onto a carrier by an impregnation method. The present invention induces Pd to nucleate in situ on the carrier and grow into a tetrahedral shape by adjusting the molar ratio of DMF and water in the solvent. This tetrahedral shape has a larger total surface energy and a more active surface. At the same time, the unique tetrahedral structure and small and evenly distributed palladium nanocrystals can provide more active sites for the catalytic reaction, and can efficiently catalyze hydrogen reduction of nitrobenzene to prepare aniline at 20°C.
[0019] The catalyst prepared by the present invention is applied to catalyze the reduction of nitrobenzene with hydrogen to prepare aniline. The nitrobenzene conversion rate reaches 100% after 35 minutes of reaction, and the selectivity of the reduction to prepare aniline is as high as 99.9%. The catalyst prepared by the preparation method of the present invention has good stability and recyclability, and still maintains high activity and high selectivity after being recycled for five times. In addition, the catalyst also has certain activity and good selectivity for catalyzing the selective hydrogenation of other aromatic nitro compounds. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 The XRD pattern of the palladium nanocatalyst prepared in Example 1;
[0021] Figure 2 TEM image of the palladium nanocatalyst prepared in Example 1;
[0022] Figure 3 HR-TEM image of the palladium nanocatalyst prepared in Example 1;
[0023] Figure 4 This is a diagram of N2 adsorption and desorption of the palladium nanocatalyst prepared in Example 1;
[0024] Figure 5 This is the BJH pore size distribution diagram of the palladium nanocatalyst prepared in Example 1;
[0025] Figure 6 This is an XPS comparison chart of the palladium nanocatalyst prepared in Example 1 and N1s in pure g-C3N4;
[0026] Figure 7 This is the XPS graph of the palladium nanocatalyst Pd 3d prepared in Example 1. DETAILED DESCRIPTION
[0027] The present invention provides a method for preparing a g-C3N4-supported palladium nanocatalyst, comprising the following steps:
[0028] The g-C3N4 solution, palladium source, bromide and coordination compound are mixed and then subjected to reduction reaction to obtain the palladium nanocatalyst.
[0029] In the present invention, the g-C3N4 solution comprises g-C3N4 and an aqueous solution of N,N-dimethylformamide;
[0030] In the present invention, the g-C3N4 solution is obtained by ultrasonication of g-C3N4 and N,N-dimethylformamide aqueous solution;
[0031] In the present invention, the ultrasound time is preferably 10 to 20 min, more preferably 12 to 18 min, and more preferably 14 to 16 min; the ultrasound frequency is preferably 15 to 30 KHz, more preferably 18 to 27 KHz, and more preferably 20 to 25 KHz.
[0032] In the present invention, the g-C3N4 can be purchased or prepared.
[0033] The present invention also provides a method for preparing g-C3N4, comprising the following steps:
[0034] The g-C3N4 is obtained by roasting and grinding the urea.
[0035] In the present invention, the calcination temperature is preferably 500-600°C, more preferably 530-570°C, and more preferably 545-555°C; the calcination heating rate is preferably 5-15°C / min, more preferably 8-12°C / min, and more preferably 9.5-10.5°C / min; the calcination holding time is preferably 2-4h, more preferably 2.5-3.5h, and more preferably 2.8-3.2h.
[0036] In the present invention, the particle size of the ground g-C3N4 is preferably 100um to 150um, more preferably 110 to 140um, and more preferably 120 to 130um.
[0037] In the present invention, the mass volume ratio of the g-C3N4 to the N,N-dimethylformamide aqueous solution is preferably 620-630 mg:10-22.5 mL, more preferably 623-627 mg:13-19.5 mL, and more preferably 624-626 mg:15-17.5 mL.
[0038] In the present invention, in the N,N-dimethylformamide aqueous solution, the molar ratio of N,N-dimethylformamide to water is preferably 0.5-1.5:0-7, more preferably 0.7-1.3:2-5, and more preferably 0.9-1.1:3-4.
[0039] In the present invention, the type of the palladium source is preferably palladium acetylacetonate or palladium chloride; the bromide is preferably sodium bromide or potassium bromide; and the ligand is preferably molybdenum hexacarbonyl.
[0040] In the present invention, the mass ratio of the palladium source to g-C3N4 is preferably 40-50:620-630, more preferably 42-48:622-628, and more preferably 44-46:624-626.
[0041] In the present invention, the mass ratio of the bromide to g-C3N4 is preferably 70-90:620-630, more preferably 75-85:622-628, and more preferably 78-82:624-626.
[0042] In the present invention, the mass ratio of the ligand to g-C3N4 is preferably 20-40:620-630, more preferably 25-35:622-628, and more preferably 28-32:624-626.
[0043] In the present invention, the temperature of the reduction reaction is preferably 70-90°C, more preferably 75-85°C, and more preferably 78-82°C; the time of the reduction reaction is preferably 10-12h, more preferably 10.5-11.5h, and more preferably 10.8-11.2h.
[0044] In the present invention, the reduction reaction results in a gray-blue suspension.
[0045] In the present invention, the obtained gray-blue precipitation solution is centrifuged, washed and dried to obtain the palladium nanocatalyst.
[0046] In the present invention, the centrifugal speed is preferably 7000-9000 r / min, more preferably 7500-8500 r / min, more preferably 7800-8200 r / min; the centrifugal time is preferably 3-6 min, more preferably 3.5-5.5 min, more preferably 4-5 min; the solvent used for washing is preferably an ethanol-acetone mixed solution.
[0047] In the ethanol-acetone mixed solution, the volume ratio of ethanol to acetone is preferably 0.5-1.5:8.5-9.5, more preferably 0.7-1.3:8.7-9.3, and more preferably 0.9-1.1:8.9-9.1; the number of washings is preferably greater than or equal to 3 times, more preferably greater than or equal to 4 times, and more preferably greater than or equal to 5 times; the drying temperature is preferably 50-70°C, more preferably 55-65°C, and more preferably 58-62°C; the drying time is preferably 22-26h, more preferably 23-25h, and more preferably 23.5-24.5h.
[0048] The invention also provides a palladium nanocatalyst obtained by the preparation method.
[0049] The invention discloses an application of the palladium nanocatalyst in catalyzing the reduction of nitroaromatic hydrocarbons by hydrogen to prepare aniline.
[0050] In the present invention, the nitroaromatic hydrocarbon is preferably nitrobenzene, 4-nitrophenol, 2-nitroaniline, 2-nitrotoluene, or 1,3-dinitrobenzene.
[0051] The technical solutions provided by the present invention are described in detail below in conjunction with the embodiments, but they should not be construed as limiting the protection scope of the present invention.
[0052] Example 1
[0053] 624 mg of g-C3N4 was dissolved in 20 mL of N, N-dimethylformamide aqueous solution (the molar ratio of N, N-dimethylformamide to water was 1:3), and ultrasonic treatment was performed at a frequency of 20 KHz for 15 min to obtain a g-C3N4 solution. Subsequently, 45 mg of Pd(acac)2, 30 mg of molybdenum hexacarbonyl, and 80 mg of sodium bromide were added to the g-C3N4 solution, and the mixed solution was heated to 80 ° C and reduced for 11 h to finally obtain a gray-blue precipitate solution;
[0054] The obtained mixed solution was centrifuged at 8000 r / min for 5 min to separate a gray-blue precipitate, which was then washed three times with an ethanol-acetone mixed solution (V ethanol:V acetone=1:9).
[0055] The washed gray-blue precipitate was placed in a drying furnace and dried at 60°C for 24 hours to finally obtain a palladium nanocatalyst.
[0056] The g-C3N4 supported palladium nanocatalyst prepared in Example 1 was subjected to XRD test, and the test results are shown in Figure 1 , 13.1 ° and 27.5 ° The diffraction peaks at 40.12 correspond to the (100) and (002) planes of the g-C3N4 support. ° ,46.66 ° , 68.12 ° and 82.1 ° The XRD diffraction peaks at correspond to the diffraction peaks of Pd (111), (200), (220) and (311) crystal planes. The diffraction peak of Pd with weaker intensity appears, indicating that the Pd particles are small in size or are uniformly dispersed on the surface of the g-C3N4 carrier.
[0057] The g-C3N4 supported palladium nanocatalyst prepared in Example 1 was subjected to TEM test, and the test results are shown in Figure 2 The g-C3N4-loaded Pd nano-tetrahedron catalyst provided by the present invention presents a two-dimensional layered structure, and the loaded Pd particles have a tetrahedral morphology, a particle size of about 6.5 nm, and are evenly dispersed.
[0058] The g-C3N4 supported palladium nanocatalyst prepared in Example 1 was subjected to HR-TEM test, and the test results are shown in Figure 3 , Figure 3 It can be seen that the diffraction fringes of the Pd nanoparticles have a lattice spacing of 0.22 nm, corresponding to the Pd (111) plane. The diffraction fringes run through the entire particle, indicating that the particle is tetrahedral in shape.
[0059] The g-C3N4 supported palladium nanocatalyst prepared in Example 1 was subjected to nitrogen adsorption and desorption test. The test results are shown in Figure 4 and Figure 5 The catalyst has a type IV adsorption isotherm with an H3-type hysteresis loop, indicating the presence of mesopores and micropores in the catalyst. Figure 4 As shown in Figure 2, a hysteresis loop appears in the part with higher relative pressure, indicating that the specific surface area of the catalyst comes from the mesopores and micropores formed by the self-assembly and bending stacking of g-C3N4 nanosheets. Figure 5 As shown, the specific surface area of the palladium nanocatalyst prepared in Example 1 is 61.19 m 2 / g, and the average pore volume is 0.18cm 3 / g, and the average pore size is 11.75nm.
[0060] XPS test was performed on the g-C3N4 supported palladium nanocatalyst prepared in Example 1. Figure 6 and 7 As shown by Figure 6 It can be seen that the binding energy of the N1s spectrum of the g-C3N4-loaded Pd nano-tetrahedron catalyst is reduced by 0.2 ev compared with the pure carrier g-C3N4, indicating that there is an interaction between the Pd nano-tetrahedron and g-C3N4. Figure 7 As shown in Figure 2, the two peaks centered at 334.7 eV and 340.0 eV are respectively attributed to the metal Pd at 3d5 / 2 and 3d3 / 2. 0 The other pair of double peaks at 336.3 eV and 341.5 eV correspond to 3d5 / 2 and 3d3 / 2 Pd 2+ , indicating that Pd nanocrystals were successfully synthesized on the carrier g-C3N4.
[0061] The palladium nanocatalyst prepared in Example 1 was used to carry out catalytic hydrogenation reaction of nitrobenzene.
[0062] The specific application method is: add a certain amount of nitrobenzene, ethanol and the g-C3N4-loaded palladium nanocatalyst prepared in Example 1 into an autoclave high-pressure reactor, fill with hydrogen, adjust the pressure to 2MPa, react at 20°C for 35 minutes, extract the reaction filtrate, dilute it appropriately, and analyze it by gas chromatography to obtain the conversion rate and selectivity results as Application Example 1, as shown in Table 1.
[0063] Example 2
[0064] Take 20g of urea and place it in a muffle furnace. Heat it to 550℃ at a heating rate of 10℃ / min. Keep it warm for 3h and then cool it naturally to 20℃. Grind the solid powder to a particle size of 100um to obtain g-C3N4.
[0065] 624 mg of g-C3N4 prepared by the above method was dissolved in 12 mL of N, N-dimethylformamide (the molar ratio of N, N-dimethylformamide to water was 1:0), and ultrasonically treated at a frequency of 20 KHz for 15 min to obtain a g-C3N4 solution. Subsequently, 45 mg of Pd(acac)2, 30 mg of molybdenum hexacarbonyl, and 80 mg of sodium bromide were added to the g-C3N4 solution, and the mixed solution was heated to 80 ° C and reduced for 11 h to finally obtain a gray-blue suspension.
[0066] The obtained suspension was centrifuged at 8000 r / min for 5 min to separate a gray-blue precipitate, which was then washed three times with an ethanol-acetone mixed solution (V ethanol:V acetone=1:9).
[0067] The washed gray-blue precipitate was placed in a drying furnace and dried at 60° C. for 24 hours to finally obtain the palladium nanocatalyst.
[0068] Example 3
[0069] Take 20g of urea and place it in a muffle furnace. Heat it to 580℃ at a heating rate of 8℃ / min. Keep it warm for 2.5h and then cool it naturally to 20℃. Grind the calcined solid powder to a particle size of ~100um to obtain g-C3N4.
[0070] 624 mg of g-C3N4 prepared by the above method was dissolved in 14.7 mL of N, N-dimethylformamide aqueous solution (the molar ratio of N, N-dimethylformamide to water was 1:1), and ultrasonically treated at a frequency of 20 KHz for 15 min to obtain a g-C3N4 solution. Subsequently, 45 mg of PdCl2, 30 mg of molybdenum hexacarbonyl, and 80 mg of sodium bromide were added to the g-C3N4 solution, and the mixed solution was heated to 80 ° C and reacted for 11 h to finally obtain a gray-blue precipitate solution;
[0071] The obtained mixed solution was centrifuged at 8000 r / min for 5 min to obtain a gray-blue precipitate, which was then washed three times with an ethanol-acetone mixed solution (V ethanol:V acetone=1:9).
[0072] The washed gray-blue precipitate was placed in a drying furnace and dried at 60° C. for 24 hours to finally obtain the g-C3N4-supported palladium nanocatalyst.
[0073] Example 4
[0074] 624 mg of g-C3N4 was dissolved in 17.5 ml of N, N-dimethylformamide aqueous solution (the molar ratio of N, N-dimethylformamide to water was 1:2), and ultrasonic treatment was performed at a frequency of 20 KHz for 15 min to obtain a g-C3N4 solution. Subsequently, 45 mg of Pd(acac)2, 30 mg of molybdenum hexacarbonyl, and 80 mg of potassium bromide were added to the g-C3N4 solution, and the mixed solution was heated to 80 ° C and reacted for 11 h to finally obtain a gray-blue precipitate solution;
[0075] The obtained mixed solution was centrifuged at 8000 r / min for 5 min to separate a gray-blue precipitate, which was then washed three times with an ethanol-acetone mixed solution (V ethanol:V acetone=1:9).
[0076] The washed gray-blue precipitate was placed in a drying furnace and dried at 60° C. for 24 hours to finally obtain the g-C3N4-supported palladium nanocatalyst.
[0077] Example 5
[0078] 624 mg of g-C3N4 was dissolved in 22.5 mL of N, N-dimethylformamide aqueous solution (the molar ratio of N, N-dimethylformamide to water was 1:4), and ultrasonic treatment was performed at a frequency of 20 KHz for 15 min to obtain a g-C3N4 solution. Subsequently, 45 mg of Pd(acac)2, 30 mg of molybdenum hexacarbonyl, and 80 mg of sodium bromide were added to the g-C3N4 solution, and the mixed solution was heated to 80 ° C and reacted for 11 h to finally obtain a gray-blue precipitate solution;
[0079] The obtained mixed solution was centrifuged at 8000 r / min for 5 min to separate a gray-blue precipitate, which was then washed three times with an ethanol-acetone mixed solution (V ethanol:V acetone=1:9).
[0080] The washed gray-blue precipitate was placed in a drying furnace and dried at 60° C. for 24 hours to finally obtain the g-C3N4-supported palladium nanocatalyst.
[0081] The palladium nanocatalysts prepared in Examples 2 to 5 were used for catalytic hydrogenation of nitrobenzene. Application Examples 2 to 5 were used for catalytic hydrogenation of nitrobenzene using the palladium nanocatalysts prepared in Examples 2 to 5.
[0082] The specific application method is the same as the catalytic hydrogenation reaction method of nitrobenzene in Example 1, the only difference being that the reaction time is 30 min.
[0083] Table 1 Test results of application examples 1 to 5
[0084]
[0085] It can be seen from Application Examples 1 to 5 that the g-C3N4-supported palladium nanocatalyst prepared by the present invention has a nitrobenzene conversion rate of 100% in the catalytic hydrogen reduction reaction of nitrobenzene to prepare aniline at 20°C, and the selectivity for aniline is as high as 99.9%.
[0086] In order to better verify the stability and recyclability of the palladium nanocatalyst obtained by the preparation method of the present invention, the inventors conducted experiments on the g-C3N4-loaded palladium nanocatalyst prepared in Example 1 according to the steps in Application Examples 1 to 5. After the reaction was terminated, the catalyst was separated and fully washed and dried with ethanol, and the dried catalyst was further subjected to cycle experiments. The first to fifth cycle experiments are Application Examples 6 to 10, respectively. The final results are shown in Table 2.
[0087] Table 2 Test results of cyclic reaction of Example 1
[0088]
[0089] The test results show that the g-C3N4-loaded palladium nanocatalyst obtained by the preparation method of the present invention can still achieve a nitrobenzene conversion rate of 96% and a selectivity for aniline of 99.9% after 5 cycles in the catalytic hydrogen reduction reaction of nitrobenzene to produce aniline. The catalyst is a catalyst with good stability and recyclability.
[0090] The catalyst prepared in Example 1 was applied to the selective hydrogenation reaction of other aromatic nitro compounds. The specific reaction conditions were the same as those in Application Examples 1 to 5, with the only difference being that the reaction temperature was adjusted. The final results are shown in Table 3.
[0091] Table 3 Catalyst universality test results
[0092]
[0093] The results are shown in Table 3. The g-C3N4 supported palladium nanocatalyst obtained by the preparation method of the present invention also has good activity and selectivity for certain nitroaromatic hydrocarbons containing other substituents.
[0094] It can be seen from the above embodiments that the present invention provides a method for preparing a g-C3N4-supported palladium nanocatalyst, comprising the following steps: mixing a g-C3N4 solution, a palladium source, a bromide and a ligand and then performing a reduction reaction to obtain the g-C3N4-supported palladium nanocatalyst. It can be seen from experimental verification that the g-C3N4-supported palladium nanocatalyst prepared by the preparation method of the present invention is applied to catalyze hydrogen reduction of nitrobenzene to produce aniline at 20°C, and the nitrobenzene conversion rate reaches 100% after 35 minutes of reaction, and the selectivity of the reduction to produce aniline is as high as 99.9%, and the catalytic effect is excellent. After five cycles of use, it still maintains high activity and high aniline selectivity. In addition, the catalyst also has certain activity and good selectivity for catalyzing the selective hydrogenation of other aromatic nitro compounds.
[0095] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. Application of a g-C3N4 supported palladium nanocatalyst in catalytic hydrogen reduction of nitroaromatics to prepare aniline, characterized in that: The preparation method of the g-C3N4-supported palladium nanocatalyst comprises the following steps: 624 mg of g-C3N4 was dissolved in 20 mL of an N,N-dimethylformamide aqueous solution, wherein the molar ratio of N,N-dimethylformamide to water was 1:3, and the solution was ultrasonically treated at a frequency of 20 KHz for 15 min to obtain a g-C3N4 solution. Subsequently, 45 mg of Pd(acac)2, 30 mg of molybdenum hexacarbonyl, and 80 mg of sodium bromide were added to the g-C3N4 solution, and the mixed solution was heated to 80° C. and subjected to a reduction reaction for 11 h to finally obtain a gray-blue precipitation solution. The obtained gray-blue precipitation solution was centrifuged, washed, and dried to obtain the g-C3N4-loaded palladium nanocatalyst. The g-C3N4-loaded palladium nanocatalyst exhibited a two-dimensional layered structure, and the loaded Pd particles had a tetrahedral morphology. The g-C3N4-loaded palladium nanocatalyst was used to catalyze the reduction of nitroaromatics with hydrogen to prepare aniline.